The professional practice of architectural working drawings - Wakita, Osamu A.; Linde, Richard M. (New York : J. Wiley and Sons, 2003)
In one beautifully illustrated volume, The Professional Practice of Architectural Working Drawings presents the full range of skills, concepts, principles, and applications needed to create a full set of architectural working drawings. This new Third Edition emphasizes the importance of communicating general design concepts through specific working drawings. Chapters proceed logically through each stage of development, beginning with site and foundation plans and progressing to elevations, building sections, and other drawings.
Chapter 1 The Office Chapter 2 Basic Drafting Requirements/Techniques Chapter 3 Computer Aided Design Drawing Chapter 4 Foundation Plans Chapter 5 Floor Plans Chapter 6 Initial Preparation Phase for Construction Documents Chapter 7 Game Plan for a Selected Material Chapter 8 Site and Grading Plan Chapter 9 Foundation Plans Chapter 10 Floor Plans Chapter 11 Schedules: Door, Window, and Finish Chapter 12 Building Sections Chapter 13 Exterior Elevations Chapter 14 Conceptual Design and Construction Documents for a Wood Building - Mountain Cabin Chapter 15 Conceptual Design and Construction Documents for a Wood Building - Beach House Chapter 16 Conceptual Design and Construction Documents for an Office Park Chapter 17 Conceptual Design and Construction Documents for a Steel and Masonry Building - Theatre Chapter 18 Case Study Chapter 19 Case Study Chapter 20 Case Study: Madison Office Building - Steel Structure Chapter 21 Tenant Improvements
Includes bibliographical references and index.
Keywords: Architecture -- Designs and plans -- Working drawings